Mixture Formation in a CNG-DI Engine in Stratified Operation - Friedrich, Wolfgang; Grzeszik, Roman; Wensing, Michael (SAE Technical Papers, 2015)
In a study using a single-cylinder engine a significant potential in fuel efficiency and emission reduction was found for stratified operation of a high pressure natural gas direct injection (DI) spark ignition (SI) engine. The control of the mixture formation process appeared to be critical to ensure stable inflammation of the mixture. Therefore, optical investigations of the mixture formation were performed on a geometric equivalent, optically accessible single-cylinder engine to investigate the correlation of mixture formation and inflammability. The two optical measurement techniques infrared (IR) absorption and laser-induced fluorescence (LIF) were employed. Mid-wavelength IR absorption appeared to be qualified for a global visualization of natural gas injection; LIF allows to quantify the equivalence ratio inside a detection level. While LIF measurements require complex equipment, the IR setup consists merely of a black body heater and a mid-wavelength sensitive IR camera. Methane, the main part of natural gas, absorbs IR radiation at about 3.4 m. The LIF technique was used to get detailed information about the charge distribution in the region of the spark plug, complementary to the global view acquired by the IR technique.
Created from Fastlane, Scopus look-up